Beyond Continuous Improvement: Unraveling the invisible challenges of implementing organizational change in a Software Industry Company - Lima, Rayfran Rocha; Oran, Ana Carolina; França, César (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de Software, 2024)
Organizational change (OC) is crucial for innovation and competitiveness in the software industry, yet companies often lack systematic processes and risk management, leading to inefficiencies and failures worsened by volunteers without OC management knowledge. This paper discusses four overlooked challenges in this area, highlighting a crucial but frequently ignored issue: the inefficiency of OC processes in the software industry. We conducted a company-wide case study to identify the familiarity and use of OC management models and practices applied by volunteers who implement large internal improvements and innovations in software development companies. The findings reveal significant challenges in OC implementation, including the lack of OC specialized knowledge, the knowledge gap about OC effective models, the dependence on exceptional individuals, and invisible or overlooked resistance. Effective OC in the software industry demands a holistic approach that harmonizes technical and managerial competencies aligned with the company’s strategic goals. Further research is needed to improve organizational change processes in the software industry, reduce resource waste, and challenge the belief that only continuous improvement ensures company survival and competitiveness.